Tlaxcala and the health sector in Mexico (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2009)
This work is an attempt to establish a rational, measurement of an entire sector, as in this case the Health, from an abundant number of independent variables, an important part of Regional Development, with special emphasis on the resources used by the State of Tlaxcala - Mexico. The measurement of development, together with the definition of the determinants of growth are two issues that have focused the interest of social scientists in general. For this study, we have the data until 2000, since in Mexico the main source of statistical information is provided by the National Institute of Statistics and Geography, INEGI, who is on their census every 10 years. So we will be publishing the results of 2010 in 2011, a situation that subsequently lead to the updating of this study 2010.
Keywords: regional development; health sector; principal components